2017
DOI: 10.1002/jbmr.3087
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally High and Heterogeneous Bone Matrix Mineralization After Childhood Solid Organ Transplantation: A Complex Pathology of Low Bone Turnover and Local Defects in Mineralization

Abstract: Chronic renal, liver, and heart failure in children associates with multiple skeletal complications. Increased fracture incidence often persists after transplantation and could be related to alterations in bone material properties. In the present cohort study we evaluated bone mineralization density distribution (BMDD) by quantitative backscattered electron imaging (qBEI) in 23 pediatric solid organ allograft recipients with suspected osteoporosis. We measured BMDD in the entire cross-sectional area of transil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(209 reference statements)
0
4
0
Order By: Relevance
“…( 26 ) Hence, within the post‐burosumab group, CnCaLow was positively associated with the number (surface extent) of osteoblasts, as expected in situations of normal bone formation. ( 40,62 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 26 ) Hence, within the post‐burosumab group, CnCaLow was positively associated with the number (surface extent) of osteoblasts, as expected in situations of normal bone formation. ( 40,62 )…”
Section: Discussionmentioning
confidence: 99%
“…(26) Hence, within the postburosumab group, CnCaLow was positively associated with the number (surface extent) of osteoblasts, as expected in situations of normal bone formation. (40,62) This temporal uncoupling between matrix formation and matrix mineralization in XLH, strongly suggests that the cells within the osteoid are responsible for the mineralization process. Such an assumption is in accordance with the growing body of evidence that mineralization starts around young osteocytes, the osteoid-osteocytes, a distinct cell population descendent from osteoblasts, which become embedded within the unmineralized matrix and are differentiating into mature osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of bone markers represent an overall assessment of the modeling and remodeling processes in the entire skeleton, which can differ between different skeletal sites and different bone compartments such as trabecular and cortical bone . Fratzl‐Zelman et al demonstrated recently a broad heterogeneity in bone matrix mineralization in pediatric solid‐organ recipients by bone histomorphometry, which further explains some of the observed alterations in bone material properties that impact skeletal fragility.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative assessment of bone mineralization is important as many metabolic diseases, and medication may affect mineralization. Examples include (high and low bone turnover) osteoporosis [9][10][11][12], osteogenesis imperfecta [13][14][15], melorheostosis [16,17], hypophosphatemia [18], hypophosphatasia [19,20] as well as bisphosphonate [21][22][23] or teriparatide [24] treatment.…”
Section: Introductionmentioning
confidence: 99%